Feasibility of Parent Training via Telehealth for Children with Autism Spectrum Disorder and Disruptive Behavior: A Demonstration Pilot - Bearss, Karen; Burrell, T. Lindsey; Challa, Saankari A.; Postorino, Valentina; Gillespie, Scott E.; Crooks, Courtney; Scahill, Lawrence (Journal of autism and developmental disorders, 2018)
Telehealth is a potential solution to limited access to specialized services for children with autism spectrum disorder (ASD) in rural areas. We conducted a feasibility trial of parent training with children ages 3–8 with ASD and disruptive behavior from rural communities. Fourteen children (mean age 5.8 ± 1.7) from four telehealth sites enrolled. Thirteen families (92.9%) completed treatment, with 91.6% of core sessions attended. Therapists attained 98% fidelity to the manual and 93% of expected outcome measures were collected at week 24. Eleven of 14 (78.6%) participants were rated as much/very much improved. Parent training via telehealth was acceptable to parents and treatment could be delivered reliably by therapists. Preliminary efficacy findings suggests further study is justified.